An Analysis Study on Teacher Strategy to Improve Speaking Skill Students in the Sixth Grade of Elementary School Diniyyah Al Azhar Jambi - Sri Mulyati (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this research is to find out what strategies are used by teacher, this study using qualitative research . The subject of this study were students at the elementary school of Diniyyah Al-azhar Jambi. Especially students in the sixth grade.This study uses several speaking Teaching strategies to improve speaking skills in the last semester Diniyyah Al azhar jambi are prepared talk on data 1,9 and 19. Discussion on data 3,5,7,18,20 and 23, questionnaires on data 2,4,11,13,15,16,17,21 and 24 and assuring that misunderstanding can occur in data11,14 and 22 and building up stock of minimal responses on data 10, researcher also use data collection methods that aim to determine the results of the research conducted. As for the data collection methods used are observation and interviews. Data were analyzed and identified with the strategy prepared previously , the speaking teaching strategies had a significant effect on teaching speaking skill , which occured in all school Diniyyah Al- Azhar Jambi.